2015
DOI: 10.2340/16501977-1899
|View full text |Cite
|
Sign up to set email alerts
|

Machines that go ”ping” may improve balance but may not improve mobility or reduce risk of falls: A systematic review

Abstract: Objective: To determine the effectiveness of computer-based electronic devices that provide feedback in improving mobility and balance and reducing falls. Data sources: Randomized controlled trials were searched from the earliest available date to August 2013. Data extraction: Standardized mean differences were used to complete meta-analyses, with statistical heterogeneity being described with the I-squared statistic. The GRADE approach was used to summarize the level of evidence for each completed meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These games use either standard or customised physical apparatus attached to a games console or computer the most common of which used is the Nintendo Wii. One study found that such games are not more effective than traditional exercise programmes [19] they have been found to be equally effective and have the advantage of delivering entertainment as an additional intentional motivation [20]. It is important to ascertain whether serious games have a role to play in promoting falls safety.…”
Section: Introductionmentioning
confidence: 99%
“…These games use either standard or customised physical apparatus attached to a games console or computer the most common of which used is the Nintendo Wii. One study found that such games are not more effective than traditional exercise programmes [19] they have been found to be equally effective and have the advantage of delivering entertainment as an additional intentional motivation [20]. It is important to ascertain whether serious games have a role to play in promoting falls safety.…”
Section: Introductionmentioning
confidence: 99%
“…In the pediatric field, De Kloet and colleagues reported that children with acquired brain injury had cognitive and motor benefits following a 12-week tailored rehabilitation program with the Nintendo Wii [ 7 ]. The rationale behind the increased application of digital therapies is to improve patients’ motivation influencing their affective response and engagement [ 8 , 9 ]. Additionally, since subjects can perceive therapeutic exercises as monotonous, an interactive approach has been demonstrated to improve the compliance of patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind the increased application of digital therapies is to improve patients’ motivation influencing their affective response and engagement [ 8 , 9 ]. Additionally, since subjects can perceive therapeutic exercises as monotonous, an interactive approach has been demonstrated to improve the compliance of patients [ 9 ]. Moreover, after completing the rehabilitation, virtual reality or gaming interventions showed improved treatment adherence, engagement [ 10 ], and quality of life over conventional treatment of upper limb functions in patients with stroke [ 11 ].…”
Section: Introductionmentioning
confidence: 99%